Pendidikan Islam Perspektif Abdullah Nashih Ulwan - Edi Iskandar (STAIN Bengkalis, 2018)
Abdullah Nashih Ulwan is a practitioner and thinker in the world of education, especially Islamic education. The discussion is divided into two papers, first, it discussed about the purpose of Islamic education, second, Islamic education curriculum, and Islamic educational institutions according to Abdullah Nashih Ulwan. This paper will be briefly summarized the history of life, and the background of this charismatic ulama thought.